The Night and Cultural Benefit: The Case for A Holistic Approach to Licensing. (12th June 2020) - Roberts, Marion; Eldridge, Adam; Osborn, Guy; Flacks, Simon
This research article critically engages with the Licensing Act (2003), arguing for a more holistic approach to licensing. Drawing on primary research conducted in London for the Greater London Authority (GLA), the article considers the benefits of licensed venues and the possibility of extending current licensing objectives to recognise the role of these venues in sustaining urban vitality. The current licensing objectives are geared towards minimising negative outcomes, the assumption being that licensing is primarily a tool of control, with the role of minimising harm. The argument developed here is based on two alternative conceptions of the role of licensing. Firstly, licensing has a key role to play in developing sites for sociability and community cohesion. Though focused around alcohol, licensing is central to enabling or constraining more traditional as well as emerging spaces which combine entertainment, dining and other experimental forms of leisure. Second, the article argues that by addressing urban vitality and cultural benefit, the Act could be more attuned to the positive influence of licensed premises on a broader scale. The need for planning and licensing to work more cooperatively is considered in light of how licensing decisions reach beyond individual venues and impact on entire neighbourhoods or areas. Focusing on two London boroughs, Croydon and Lambeth, the paper examines how the current approach to licensing by local authorities could therefore be re-framed in more positive terms to acknowledge the wider cultural benefits and social good of licensed premises.